Unit Cost Calculation of CT Scan Services based on Step-Down Method: A Case Study of Iran - Kaveh Houman; Alireza Ghorbani; Behrouz Fathi; Bahram Nabilou; Hasan Yusefzadeh (Shiraz University of Medical Sciences, 2024)
Background: CT-scan is one of the radiology units in which various services are carried out by injection and without injection to describe the patient's anatomy better. Given the increasing costs of the CT due to diagnostic equipment, it is necessary to calculate the exact costs of services provided to determine optimal pricing and logical tariff of these services.Methods: The present study is an applied and cross-sectional research performed by step-down costing method using the data of 2018 at the CT-scan unit of the radiology department of Imam Reza Hospital in Urmia. In this study, standard forms related to direct and indirect costs of CT units and other activity centers have been used to collect the data. Appropriate sharing bases were used to determine the share of the costs of other departments in the services of this unit.Results: The cost of a brain scan without injection was calculated 66.7$PPP, the brain with injection 143.9$, the chest without injection 84.4$PPP, the chest with injection 163.5$PPP, upper and lower limbs without injection 150.1$PPP, spine (cervical, thoracic, lumbar) 135.6$PPP, abdomen and pelvis without injection 149.2$PPP, abdomen and pelvis with injection 243.9$PPP, sinus 94.1$PPP, carotid CT angiography (extracranial) 287.5$PPP, and thoracic aortic CT angiography 277.8$PPP.Conclusion: The study results showed a significant difference between the actual price of CT scan services and tariffs. Also, the shorter the service time and the more services in the CT scan department, the lower the unit cost. Comparing the cost of selected CT services in this study, we found that some timeconsuming services, which were mainly related to injection services, imposed higher costs on the centers.